2022
DOI: 10.1097/meg.0000000000002502
|View full text |Cite
|
Sign up to set email alerts
|

Frailty as tested by the Liver Frailty Index in out-patient patients with cirrhosis in China: a cross-sectional study

Abstract: Background Early identification and prevention of frailty are very important for patients with cirrhosis. Methods The study was the first to use Liver Frailty Index in out-patient patients with cirrhosis in China, and to analyze the influencing factors. Result This study included 387 patients with cirrhosis. Frailty was diagnosed using the Liver Frailty Index. Multiple Logistic regression model were used to analyze influencing factors of frailty in out-patient patients with cirrhosis. Frailty was diagnosed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…To better characterize the distribution of age, sex, and BMI in cirrhotic patients with frailty, we performed meta-analyses for subgroups separately in the frail and non-frail cohorts from five studies ( 19 , 21 23 , 25 ). Through the subgroup analysis, we found that the cirrhosis patients in the frail cohort tend to have a higher age, with a mean age of 63.3 (95% CI: 59.9, 66.7; Z = 36.48; P < 0.001), and a larger proportion of male patients, with a mean of 73.5% (95% CI: 71.4, 75.5%; Z = 7.65; P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better characterize the distribution of age, sex, and BMI in cirrhotic patients with frailty, we performed meta-analyses for subgroups separately in the frail and non-frail cohorts from five studies ( 19 , 21 23 , 25 ). Through the subgroup analysis, we found that the cirrhosis patients in the frail cohort tend to have a higher age, with a mean age of 63.3 (95% CI: 59.9, 66.7; Z = 36.48; P < 0.001), and a larger proportion of male patients, with a mean of 73.5% (95% CI: 71.4, 75.5%; Z = 7.65; P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings also reveal that the cirrhosis patients in the frail cohort tend to have a higher age when compared to the non-frail cohort. However, it should be noted that a recent report found that cirrhosis patients may also experience frailty at a younger age ( 23 ). Together with our findings, aged cirrhosis patients require more frequent evaluation in clinics.…”
Section: Discussionmentioning
confidence: 99%
“…The LFI has good sensitivity and specificity in predicting frailty in patients with liver cirrhosis, with a correlation coefficient for the LFI group of 0.93 (95% confidence interval [CI], 0.91-0.95) (Lai et al, 2017). Using this tool, Li et al found that the incidence rates of frailty, prefrailty and nonfrailty were 9.6%, 54.8% and 35.6%, respectively (Li et al, 2023).…”
Section: Measurement Of Frailtymentioning
confidence: 99%
“…Frailty is a clinical state characterised by a decreased physiological reserve and an increased vulnerability to stressors (Morley et al., 2013 ). Due to the lack of standardised tools that assess cognitive dysfunction (Li et al., 2023 ) in patients with liver cirrhosis, frailty mainly presents as physical frailty, which is characterised by reductions in muscle contractility, leading to decreased physical function, functional performance and disability (Tapper et al., 2015 ). Frailty is common among patients with cirrhosis, and its prevalence increases with liver disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to assessing frailty in hospitalized patients, the LFI is also employed to diagnose frailty in out-patient individuals with cirrhosis, making it a versatile tool that can be used in a variety of healthcare settings[ 155 ]. Compared to the Karnofsky Performance Status scale, which only measures one aspect of frailty, the LFI is a more comprehensive and accurate tool for assessing the risk of mortality as it captures multiple components of frailty[ 156 ].…”
Section: Assessment Of Frailty In Liver Diseasesmentioning
confidence: 99%